2016
DOI: 10.4236/jbm.2016.44010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rac1/p38 and ERK-Dependent Cytosolic Phospholipase A<sub>2</sub> Activation in <i>Porphyromonas gingivalis</i>-Evoked Induction in Matrix Metalloproteinase-9 (MMP-9) Release by Salivary Gland Cells

Abstract: How to cite this paper: Slomiany, B.L. and Slomiany, A. (2016) Role of Rac1/p38 and ERK-Dependent Cytosolic Phospholipase A 2 Activation in Porphyromonas gingivalis-Evoked Induction in Matrix Metalloproteinase-9 (MMP-9) Release by Salivary Gland Cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Moreover, these responses to P. gingivalis are mediated through the LPS triggered TLR4 activation [18] [33].…”
Section: Lps-induced Tlr4 Activation and Mmp-9 Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, these responses to P. gingivalis are mediated through the LPS triggered TLR4 activation [18] [33].…”
Section: Lps-induced Tlr4 Activation and Mmp-9 Expressionmentioning
confidence: 99%
“…Therefore, taking into account the evidence that MMP-9 undergoes extensive processing in the Golgi network and the fact that oral mucosal inflammatory responses to P. gingivalis are characterized by the rapid rise in MMP-9 release, we investigated the nature of factors involved in the processing of signaling cascade initiated by the LPS [18]. As summarized in Figure 2, our findings demonstrated that P. gingivalis LPS-elicited induction in the salivary gland acinar cell MMP-9 release is associated with MAPK, ERK and p38 activation, and occurs with the involvement of Rac1 and cPLA 2 ).…”
Section: Lps-induced Tlr4 Activation and Mmp-9 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oral mucosal responses to P. gingivalis and its key endotoxin, cell-wall lipopolysaccharide (LPS), are characterized by the disturbances in nitric oxide synthase and cyclooxygenase systems, up-regulation in EGFR and MAPK activation, and induction in the secretion of highly glycosylated endopeptidase, metalloproteinase-9 (MMP-9) [4] [5] [6] [7] [8]. Similarly, to other regulated secretory proteins, the processing of MMP-9 along the endoplasmic reticulum (ER), Golgi, and trans-Golgi network (TGN) remains under a strict control of factors that affect the membrane recruitment and activation of various coat and cargo proteins, including ADPribosylation factors (Arfs) and protein kinase D (PKD), [9] [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%